Sino-Korean screen connections: towards a history in fragments. Issue 3 (1st September 2016) - Berry, Chris
ABSTRACT: How can we pursue the original drive of work on transnational cinema to combat methodological and ideological nationalism, but without becoming complicit with globalization and its ideology? This essay proposes researching Sino-Korean screen connections. It opens up five directions, illustrating each with a particular example: (1) revealing the occluded, illustrated by the role of Korean filmmakers in the Shanghai cinema of the colonial era; (2) understanding the transnational as composed of what Anna Tsing calls distinct 'transnational projects' that exceed globalization, such as the popularity of North Korean films in the People's Republic of China during the Cultural Revolution; (3) showing that there is no 'smooth space' of global flows, contrasting the relative absence of South Koreans in Chinese films with the much higher profile of Chinese in South Korean films; (4) looking at transborder production cultures, using the little-known example of South Koreans working in Hong Kong in the 1960s and 1970s; and (5) researching exhibition and distribution, such as the traces of the popularity of South Korean melodramas in Taiwan in the 1960s. Taking these examples, the essay asks what kind of history of Sino-Korean film connections can be written. It argues that the only possibility is a disjunctural history of fragments. Precisely because modernity demands that history take up the form of a teleological progress, disjuncture acts as a counter-history, revealing modernity's violence.